Validación del método analítico por HPLC para la disolucion de tabletas de glibenclamida 5 mg en medio de disolución con ph 7,5 - Castillo Cueva, Luis Humberto (2016)
In this research was validated a method for quantification of glibenclamide 5 mg tablets in dissolution tests using a chromatographic analytical method, HPLC, using the following characters validated analytical performance: linearity, accuracy, precision; addition analyte stability in the dissolution medium and interference filter was determined. With respect to the linearity coefficient of determination was obtained 0.9999, the relative standard deviation of precision was 0.14%, for the case of accuracy were obtained as recovery rates 97.6% (standard 20%) , 99.1% (standard 60%) and 99.9% (standard 100%), to analyte stability for both the standard and the samples obtained in solution the recoveries obtained were in the range of 98% - 102% for the interference filter, regenerated cellulose filters with pore 0.45 μm and 0.2 μm obtaining recovery rates of 100.3% and 100.2%, respectively were used. Then these results it can be concluded that the method is valid to quantify glibenclamide in dissolution tests with pH 7.5 medium